Rol del antropólogo forense en las pericias somatológicas y facial en la Unidad Médico Legal II Loreto 2025 - Pupuche Pacaya, Betsy Mariel (Universidad Nacional de la Amazonía Peruana, 2025)
The thesis “Role of the forensic anthropologist in somatological and facial expertise in the Legal Medical Unit II Loreto 2025” analyzes how the forensic anthropologist works within the legal system of Loreto, specifically in somatological and facial expertise. 24 expert reports carried out between 2022 and 2025 were reviewed, focused on cases of aggravated robbery. The study shows that, although standardized methods are applied (such as morphological-comparative analysis and the use of software such as Amped FIVE), the results are affected by low image quality, inadequate angles and facial coverage. The results: 21 reports with partial coincidence, 2 with full identification and 1 inconclusive. It is highlighted that the work of the anthropologist is not only technical, but directly influences judicial decisions, especially in regions like Loreto, where there is often no other type of evidence. The thesis also includes methodological, ethical reflections and personal experiences of the investigator, which show the real challenges of forensic work in a region with few resources. The main contribution: make visible a key but little-recognized work within the criminal process, and demonstrate that, with few means, forensic experts in Loreto manage to technically support decisions that affect the freedom or conviction of a person

La tesis “Rol del antropólogo forense en las pericias somatológica y facial en la Unidad Médico Legal II Loreto 2025” analiza cómo trabaja el antropólogo forense dentro del sistema legal de Loreto, específicamente en peritajes de tipo somatológico y facial. Se revisaron 24 informes periciales realizados entre 2022 y 2025, enfocados en casos de robo agravado. El estudio muestra que, aunque se aplican métodos estandarizados (como el análisis morfológico-comparativo y el uso de software como Amped FIVE), los resultados se ven afectados por la baja calidad de las imágenes, ángulos inadecuados y cobertura del rostro. Los resultados: 21 informes con coincidencia parcial, 2 con identificación plena y 1 no concluyente. Se destaca que el trabajo del antropólogo no solo es técnico, sino que influye directamente en decisiones judiciales, sobre todo en regiones como Loreto, donde muchas veces no hay otro tipo de evidencia. La tesis también incluye reflexiones metodológicas, éticas y experiencias personales de la investigadora, que muestran los retos reales del trabajo forense en una región con pocos recursos. El aporte principal: visibilizar un trabajo clave pero poco reconocido dentro del proceso penal, y demostrar que, con pocos medios, los peritos forenses en Loreto logran sostener técnicamente decisiones que afectan la libertad o condena de una persona.
Keywords: Antropología forense; Pericia facial; Pericia somatológica; https://purl.org/pe-repo/ocde/ford#5.03.01